A Novel δ-Hemolysis Screening Method for Detecting Heteroresistant Vancomycin-Intermediate Staphylococcus aureus and Vancomycin-Intermediate S. aureus - Cafiso, V. (American Society for Microbiology, 2012)
We assessed a new screening method, based on δ-hemolysin production in the presence of 6 mg/liter vancomycin, to distinguish heteroresistant vancomycin-intermediate Staphylococcus aureus (hVISA) and vancomycin-intermediate S. aureus (VISA) from vancomycin-susceptible S. aureus (VSSA). On 37 clinical methicillin-resistant S. aureus (MRSA) isolates, hVISA and VISA displayed no δ-hemolysis whereas VSSA displayed strong δ-hemolysis, showing 91.6% sensitivity. These data, supported by real-time reverse transcription PCR (real-time RT-PCR) highlighting an hld downregulation, i.e., VSSA>hVISA>VISA, define this new assay as a valid screening method.